Knife of dreams eaudiobook - Jordan, Robert (Wheel of Time, 2017)
The Wheel of Time is now an original series on Prime Video, starring Rosamund Pike as Moiraine! In Knife of Dreams , the eleventh novel in Robert Jordan's #1 New York Times bestselling epic fantasy series, The Wheel of Time®, Tarmon Gai'don, the Last Battle, is upon Rand al'Thor—and now the Dragon Reborn must confront the Dark One as humanity's only hope. The dead are walking, men die impossible deaths, and it seems as though reality itself has become unstable... Abandoning Rand's war against the Dark One, Perrin Aybara has made his own truce with the Seanchan in his obsessive quest to save his wife Faile from the Shaido and destroy their mutual enemies. To achieve victory, Perrin must render the Shaido Wise One channelers in Malden powerless. But even as he puts his desperate plan into action, Masema Dagar, the Prophet of the Dragon, moves against him. Traveling with circus performers through Seanchan-controlled Altara, Mat Cauthon attempts to court Tuon, the Daughter of the Nine Moons, to complete their fateful prophesized marriage. Despite being surrounded by Seanchan seeking to kill her, Mat's intended leads him on a merry chase while he wages guerrilla warfare to protect her. Knowing he cannot defeat the Dark One while at war with the Seanchan, Rand brokers for a truce with the Daughter of the Nine Moons. Unaware of Tuon's actual location, the Dragon Reborn walks into a trap set by the Forsaken Semirhage, who possesses knowledge about his powers that will either shatter or steel his resolve in the forthcoming conflict. Since its debut in 1990, The Wheel of Time® by Robert Jordan has captivated millions of readers around the globe with its scope, originality, and compelling characters. The last six books in series were all instant #1 New York Times bestsellers, and The Eye of the World was named one of America's best-loved novels by PBS's The Great American Read. The Wheel of Time® New Spring: The Novel #1 The Eye of the World #2 The Great Hunt #3 The Dragon Reborn #4 The Shadow Rising #5 The Fires of Heaven #6 Lord of Chaos #7 A Crown of Swords #8 The Path of Daggers #9 Winter's Heart #10 Crossroads of Twilight #11 Knife of Dreams By Robert Jordan and Brandon Sanderson #12 The Gathering Storm #13 Towers of Midnight #14 A Memory of Light By Robert Jordan and Teresa Patterson The World of Robert Jordan's The Wheel of Time By Robert Jordan, Harriet McDougal, Alan Romanczuk, and Maria Simons The Wheel of Time Companion By Robert Jordan and Amy Romanczuk Patterns of the Wheel: Coloring Art Based on Robert Jordan's The Wheel of Time